Laparoscopic repeat liver resection for hepatic epithelioid hemangioendothelioma - Fumihiro Terasaki; Yusuke Yamamoto; Teiichi Sugiura; Yukiyasu Okamura; Takaaki Ito; Ryo Ashida; Katsuhisa Ohgi; Katsuhiko Uesaka (Surgical Case Reports, 2020)
Abstract Background Optimal treatment for patients with hepatic epithelioid hemangioendothelioma (HEHE) remains unclear. Laparoscopic repeat liver resection (LR) is a minimally invasive and potentially effective surgical option for multiple HEHEs. Case presentation A 42-year-old woman with no relevant history was admitted for multiple liver tumors. Six tumors were observed on T2-weighted magnetic resonance imaging (MRI) including one in S2, two in S3, two in S7, and one in S8. Pathological evaluation of percutaneous tumor biopsy tissue suggested a diagnosis of HEHE and laparoscopic LR was planned. The procedure began with partial resection of S7 and partial resection of S8 and left lateral sectionectomy were performed. Another tumor was found intraoperatively on the surface of S6, necessitating removal by partial resection. Pathological evaluation of the resected tumor tissue from all seven tumors concurred with that of the preoperative biopsy. The patient was discharged on postoperative day 6 without any complications. A follow-up MRI 15 months after the primary surgery revealed one tumor each in S4, S6, and S8. Laparoscopic repeat LR was performed. The patient was discharged on postoperative day 5 without any complications. All three recurrent tumors were pathologically confirmed as HEHEs. Conclusions We successfully treated primary and recurrent HEHEs with laparoscopic LR, which is a reasonable minimally invasive procedure considering the possibility of multiple courses of liver surgery in patients with HEHE.